FRI0468 Abnormal oesophageal motility during a solid test meal in systemic sclerosis – detection in very early disease and association with disease progression. (12th June 2018) - Bütikofer, S.; Jordan, S.; Sauter, M.; Hollenstein, M.; Heinrich, H.; Freitas-Queiroz, N.; Kuntzen, T.; Valli, P.; Ang, D.; Oberacher, M.; Maurer, B.; Schwitzer, W.; et al.
Abstract : Background: Ineffective oesophageal motility (IEM) is frequent in patients with systemic sclerosis (SSc). High-resolution oesophageal manometry (HRM) is the reference standard test for oesophageal motility and addition of a test meal increases diagnostic sensitivity and specificity. Objectives: This study assessed whether using a test meal instead of standard water swallow in HRM increases sensitivity and can detect clinically relevant, abnormal motility in already very early SSc and whether this finding is associated with subsequent disease progression. Methods: This prospective, longitudinal cohort study recruited 68 consecutive SSc patients (group #1: 32 established disease (ACR/EULAR 2013 and ACR 1980 criteria fulfilled); group #2: 24 early disease (only ACR/EULAR 2013 fulfilled); group #3: 12 very early disease (clinical expert diagnosis of SSc, no classification criteria fulfilled) and 72 healthy controls. HRM evaluated oesophageal motility for water swallows and a solid test meal using validated methods. Results: SSc patients had less frequent effective oesophageal contractions during the test meal compared to healthy controls. Notably, this was detected even in very early disease (0.15, 1.0, 2.1/min for group #1, #2 and #3, vs. 2.5/min in health, p<0.001; p<0.001 and p<0.009, respectively). No other significant abnormality on HRM was found in patients with very early disease (group 1). Ineffective motility at HRM was associated with a higher modified Rodnan skin score at baseline. Moreover, at mean 18 10–31 months follow-up, the presence of ineffective motility at baseline was associated with progression of skin disease for the overall SSc cohort (p<0.010). In a secondary analysis, below-average lower oesophageal sphincter pressure was associated with progression of skin disease and organ disease, in particular interstitial lung disease (p<0.009). Conclusions: Ineffective motility during a test meal is present already in patients with very early SSc. In cross-sectional analysis, findings on HRM studies at baseline are associated with disease severity and prospectively with progression of skin disease during follow-up. Thus, performance of HRM already in very early disease stages can support individual risk-stratification of SSc patients. Disclosure of Interest: S. Bütikofer Consultant for: Consultancies<$10000, Speakers bureau: Speaking fees<$10000, S. Jordan: None declared, M. Sauter: None declared, M. Hollenstein: None declared, H. Heinrich: None declared, N. Freitas-Queiroz: None declared, T. Kuntzen Consultant for: Consultancies<$10000, Speakers bureau: Speaking fees<$10000, P. Valli: None declared, D. Ang: None declared, M. Oberacher: None declared, B. Maurer: None declared, W. Schwitzer: None declared, M. Fox Grant/research support from: Nestle Research International, AstraZeneca R and D, Given Imaging, and Reckitt Benckiser, Consultant for: Given Imaging, AstraZeneca, Reckitt Benckiser, Shire, Almirall and Sucampo., Speakers bureau: Given Imaging, Medical Measurement Systems and Sandhill Scientific Instruments., O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Mitsubishi Tanabe Pharma and Roche, Consultant for: Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa and UCB, B. Misselwitz Speakers bureau: Speaking fees<$10 000 for Given Imaging